Inclusión tecnológica de los niños de educación básica de las escuelas fiscales urbanas del cantón Zamora - Caraguay Satama, Johanna Patricia (2014)
The contribution of this paper is promoting the development of new skills and technology skills in children from Urban Elementary Schools in the province of Zamora Chinchipe of Ecuador that will allow them to perform better in the twenty-first century through Alice as a programming tool. Upon completion of this work we want to achieve career establish critical thinking skills, creativity and problem-solving skills in students of basic education urban schools in the province of Zamora. Another objective of this work is to impart basics of programming in children 6th year basic education of these educational institutions.